UJI AKTIVITAS ANTIOKSIDAN BEBERAPA EKSTRAK ALGA COKLAT Sargassum polycystum DAN Turbinaria deccurens ASAL PULAU DUTUNGAN SULAWESI SELATAN TERHADAP RADIKAL DPPH - Fitriyanti Jumaetri Sami; Nunuk Hariani Soekamto; Firdaus Firdaus; Jalifah Latip (Universitas Airlangga, 2019)
This study used S. polycystum and T. deccurens were extracted with various solvents (n-hexane, ethyl acetate and ethanol) to determine phytochemical screening and antioxidant activities. Extraction of samples by maceration method, antioxidant activity assay using the immersion method of DPPH (1,1-Diphenyl-2-picryl Hidrazil) measured absorption at a wavelength of 515 nm and compared with the control of antioxidant vitamin C. The results showed that antioxidant activity of the methanol, ethyl acetate, n-hexane extract of S. polycystum have low antioxidant activity with the value IC50 340,06, 180,54, and 502,25 mg/mL. Methanol, ethyl acetate, n-hexane extracts of T. deccurens have low antioxidant activity with value IC50 491,02, 411,80, and 502,7 mg/mL. This potential is lower than vitamin C IC50 value of 1,72 mg/mL.